Analisis Pengaruh CAR, NPL, LDR dan BOPO Terhadap Profitabilitas Bank Umum di Indonesia Tahun 2019-2022 - Arizal Putra Pratama; Syamsurizal -; Ratri Kurniasari; Azwar - (Jurusan Administrasi Niaga Politeknik Negeri Jakarta, 2023)
During the Covid-19 pandemic during 2020-2022, world economic conditions were uncertain, as were economic conditions in Indonesia. Government policies that limit people's activities to suppress the spread of the corona virus are a challenge for banks in Indonesia to carry out their functions as business entities that collect and distribute public funds. This study aims to examine the effect of CAR, NPL, LDR, and BOPO ratios on the profits of commercial banks in Indonesia during 2019-2022. In that year, conditions before the pandemic can be seen, namely 2019, until the provisions on community activity restrictions are lifted, namely 2022. One of the indicators in assessing bank performance is by analyzing the condition of the bank's financial statements. Analysis of financial statements is carried out by analyzing financial ratios that will affect the achievement of profits from a bank. Profit is the main goal of all business activities carried out by banks. During 2019-2022, the profits of commercial banks in Indonesia experienced a decline during the first year that the Covid-19 pandemic hit Indonesia. However, in the following years, banks in Indonesia can adapt and succeed in increasing their profits every year, until 2022